Properties of Mortar Containing Waste Glass and Limestone Filler - Karamanoğlu, B; Eren, Özgür (My University, 2008)
The building material industry has been developed due to the increasing population. This brings chronic shortage of building materials. According to this the civil engineers have been challenged to convert the industrial wastes to useful building and construction materials. The purpose of using ground waste glass is protect the environment by saving more landfills, to increase the cement plant capacity by using more beneficial additives, and to reduce CO2 emission per ton of cement by consuming less cement. This research was focused on the production of mortars containing various proportions of waste glass and limestone filler. Waste glass and limestone filler was replaced with cement by weight. Produced mortars were tested against fresh and hardened properties on specified ages. At the end of experimental study, a statistical analysis of unit weight, flow table, compressive strength, flexural strength, porosity, absorption and drying shrinkage test results are given. Different relations were found between the replacement of cement with waste glass and replacement of cement with limestone filler. The results indicate that, finer particle size and certain proportion of waste glass and limestone filler could behave satisfactory compared to the plain mortar.
Keywords: Waste glass; limestone filler; flow table; porosity; drying shrinkage